Nanocellulose Addition to Paper and the ‘Cai Lun Principle’ – Maybe Not Such a Good Idea After All - Martin A. Hubbe (BioResources)
Family groups in the ancient cultures of China, Korea, and Japan have toiled for generations in an effort to out-compete their neighbors in the pursuit of handmade paper products having better strength performance, in addition to flatness, uniform appearance, and other desirable attributes. Study of the history of the papermaking craft reveals a remarkable ability of ancient peoples to discover advantageous ways to prepare the cellulosic pulp, to improve its brightness, and to form uniform and strong paper sheets. But though the ancients knew how to “beat” the pulp to improve its bonding ability, there is no evidence of any of them having attempted to greatly “over-beat” some of the fiber, thus making nanocellulose, for potential addition to the fiber mixture. Why not? In this editorial, it is proposed that the ancients may have discovered that adding very highly fibrillated cellulose material to paper was not a good idea.